Differential between Protein and mRNA Expression of CCR7 and SSTR5 Receptors in Crohn's Disease Patients - Nathalie Taquet; Serge Dumont; Jean-Luc Vonesch; Didier Hentsch; Jean-Marie Reimund; Christian D. Muller (Hindawi Limited, 2009)
Crohn's disease (CD) is a multifactorial chronic inflammatory bowel disease of unknown cause. The aim of the present study was to explore if mRNA over-expression of SSTR5 and CCR7 found in CD patients could be correlated to respective protein expression. When compared to healthy donors, SSTR5 was over-expressed 417 ± 71 times in CD peripheral blood mononuclear cells (PBMCs). Flow cytometry experiments showed no correlation between mRNA and protein expression for SSTR5 in PBMCs. In an attempt to find a reason of such a high mRNA expression, SSTR5 present on CD PBMCs were tested and found as biologically active as on healthy cells. In biopsies of CD intestinal tissue, SSTR5 was not over-expressed but CCR7, unchanged in PBMCs, was over-expressed by 10 ± 3 times in the lamina propria. Confocal microscopy showed a good correlation of CCR7 mRNA and protein expression in CD intestinal biopsies. Our data emphasize flow and image cytometry as impossible to circumvent in complement to molecular biology so to avoid false interpretation on receptor expressions. Once confirmed by further large-scale studies, our preliminary results suggest a role for SSTR5 and CCR7 in CD pathogenesis.